Safety and immunogenicity of live, attenuated intranasal Bordetella pertussis vaccine (BPZE1) in healthy adults. Issue 47 (8th November 2022) - Buddy Creech, C.; Jimenez-Truque, Natalia; Kown, Naomi; Sokolow, Katherine; Brady, Eric J.; Yoder, Sandra; Solovay, Ken; Rubin, Keith; Noviello, Stephanie; Hensel, Elizabeth; Selamawi, Semhal; Bakare, Adetunji; et al.
Highlights: BPZE1 is a live, attenuated intranasal pertussis vaccine. BPZE1 was not associated with clinically significant adverse events after vaccination. BPZE1 induced both humoral and mucosal antibody responses after vaccination. No prolonged shedding of BPZE1 was observed. Abstract: Background: BPZE1 is a live, attenuated pertussis vaccine derived from B. pertussis strain Tohama I modified by genetic removal or inactivation of 3 B. pertussis toxins: pertussis toxin, dermonecrotic toxin, and tracheal cytotoxin. This Phase 2a study evaluated the safety and immunogenicity of liquid or lyophilized BPZE1 vaccine administered intranasally by needleless tuberculin syringe or mucosal atomization device (VaxINator TM ) at two dose levels. Methods: Fifty healthy male and non-pregnant female participants 18–49 years of age were enrolled. Participants were randomized 3:3:3:1 to a single lyophilized dose of 10 7 colony forming units (CFU) BPZE1, 10 9 CFU BPZE1, placebo via VaxINator device, or a single liquid dose of 10 9 CFU BPZE1 via tuberculin syringe. Reactogenicity was assessed for 14 days. Blood was obtained pre-vaccination; on Day 8 (safety); and on Days 15, 29, and 181 (immunogenicity). Nasal wick and swab samples were obtained at baseline and on Days 29 and 181 for assessment of mucosal antibody responses and clearance of BPZE1. Results: Across all groups, 35/50 (70 %) experienced at least one local adverse event (AE) and 31/50 (62 %) experienced at least one systemic AE, with similar AE frequencies observed between the highest 10 9 CFU BPZE1 and placebo groups. There were no severe or serious AEs during the study. At Day 29, seroconversion (≥2-fold rise from baseline in serum IgG or IgA) to at least 2 pertussis antigens was observed in 73 % in the 10 9 CFU BPZE1 VaxINator group, 60 % in the 10 9 CFU BPZE1 group delivered via tuberculin syringe, 27 % of participants in the 10 7 CFU BPZE1 VaxINator group, and 20 % in the placebo VaxINator group. No participants were colonized with BPZE1 at Day 29 post vaccination. Discussion: Lyophilized BPZE1 vaccine was well tolerated and immunogenic at the highest dose (10 9 CFU) delivered intranasally by VaxINator device and was not associated with any SAEs or prolonged shedding of BPZE1. Further evaluation of BPZE1 is warranted.